Internal Factors and its Impact on Iranian Foreign Policy - Fiedler, Radosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The Islamic Republic of Iran has a political structure with co-shared and competitive activity in the field of foreign policy. There are two power centres the president and the supreme leader. Iranian political elite is composed of factions of the conservatives, moderates, pragmatists, and reformers. Each faction has influence on the course of Iranian foreign policy. The dominant faction, conservatives, has caused isolation and imposition of severe sanctions on Iran during Ahmadinejad’s presidency Although domestic sources of foreign policy reveals competition among different factions there is consensus in principal goals of Iranian foreign policy.

W Islamskiej Republice występują dwa ośrodki władzy, które współdecydują w zakresie polityki zagranicznej Iranu. Najszersze prerogatywy posiada Najwyższy Przywódca, a jedynie pewien zakres kompetencji w polityce zagranicznej posiada prezydent. Mimo to, dochodzi do różnego rodzaju napięć oraz rozbieżności w formułowaniu polityki zagranicznej. Dodatkowym czynnikiem wywierającym wpływ na wspomniane ośrodki władzy są następujące frakcje: konserwatywna, umiarkowana, pragmatyczna i reformatorska. Przedstawiciele poszczególnych frakcji rywalizują ze sobą, także chcą mieć wpływ na politykę zagraniczną
CZYNNIKI WEWNĘTRZNE I ICH WPŁYW NA POLITYKĘ ZAGRANICZNĄ IRANU
Keywords: Iran; Foreign Policy; Supreme Leader; Iran; polityka zagraniczna; Najwyższy Przywódca